Sleep and weight-height development - Camila dos Santos El Halal; Magda Lahorgue Nunes (Elsevier, 2019)
Objectives: To describe the association between sleep duration and weight-height development in children and adolescents. Source of data: A non-systematic search in the MEDLINE database was performed using the terms anthropometry, body composition, overweight, obesity, body mass index, growth, length, short stature, sleep, children, and infants and adolescents, limited to the last 5 years. The references cited in the revised articles were also reviewed, when relevant. Synthesis of data: Sleep disorders are prevalent in the pediatric population. Among them, insomnia, which leads to a reduction in total sleep time, is the most prevalent disorder. Evidence found in the current literature allows the conclusion that sleep time reduction has a role in the current pandemic of overweight and obesity. Studies associating sleep deprivation and deficit in height growth are still insufficient. Conclusions: The association between shorter sleep duration and risk of overweight and obesity is well established for all pediatric age groups. However, more evidence is needed to establish an association between insufficient sleep duration and height growth deficit. Pediatricians should include the encouragement of healthy sleep habits in their routine guidelines as an adjuvant in the prevention and management of excess weight. Resumo: Objetivos: O objetivo deste artigo é descrever a associação entre a duração de sono e o desenvolvimento pondero-estatural entre crianças e adolescentes. Fontes de dados: Foi realizada uma busca não-sistemática na base de dados MEDLINE utilizando os termos antropometria, composição corporal, sobrepeso, obesidade, índice de massa corporal, crescimento, comprimento, baixa estatura, sono, crianças, lactentes e adolescentes, limitadas aos últimos cinco anos. As referências citadas nos artigos revisados também foram, conforme relevância, revisados. Síntese dos dados: Distúrbios do sono são prevalentes na população pediátrica. Dentre eles, a insônia, que cursa com redução do tempo total de sono, é a mais prevalente. Evidências presentes na literatura atual permitem apontar que a redução do tempo de sono tem um papel na pandemia atual de sobrepeso e obesidade. Os estudos que associam a privação de sono com déficit no crescimento estatural ainda são insuficientes. Conclusões: A associação entre menor duração de sono e risco para sobrepeso e obesidade está bem estabelecida para todas as faixas etárias da pediatria. Entretanto, maiores evidências são necessárias para que se possa estabelecer uma associação entre duração insuficiente de sono e déficit no crescimento estatural. O médico pediatra deve incluir nas suas orientações de rotina o estímulo a hábitos de sono saudáveis como coadjuvante na prevenção e manejo do excesso de peso. Keywords: Body composition, Body mass index, Growth, Sleep, Children, Adolescents, Palavras-chave: Composição corporal, Índice de massa corporal, Crescimento, Sono, Crianças, Adolescentes